(2x+1)(3x+1)=0

Simple and best practice solution for (2x+1)(3x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+1)(3x+1)=0 equation:



(2x+1)(3x+1)=0
We multiply parentheses ..
(+6x^2+2x+3x+1)=0
We get rid of parentheses
6x^2+2x+3x+1=0
We add all the numbers together, and all the variables
6x^2+5x+1=0
a = 6; b = 5; c = +1;
Δ = b2-4ac
Δ = 52-4·6·1
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1}=1$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-1}{2*6}=\frac{-6}{12} =-1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+1}{2*6}=\frac{-4}{12} =-1/3 $

See similar equations:

| 10x+4=124 | | 15=1.5/t | | (x+16)^2=21 | | 300/4=x/99 | | 6a=4(a-3)+8a= | | x 1.8=2.5 3.6 | | 7/9x+6.1=-6.9 | | -5.3+3/8x=2.7 | | -5=-3+p/2 | | 410−x 7+70=120 | | -12x^2-8x-1=0 | | 4y+2=-1/3=(8-12y) | | -24.26674+0.1x=-193(1-4.2x) | | 9x+13=x-35 | | n-2=1200 | | 2(-6y+7)-9=14 | | 9x=6x+150 | | -53y+23=-7y-34 | | 3x+(0.5x+34)=90 | | 14+6a-8=-18 | | 4+2x+19=6-x | | 3x+14=35+2 | | 7x+(3x+1)+46=180 | | -7n=-126 | | 3.5x+34=90 | | 4y+87=4y | | -1+2x=4+-3x | | p/13=17 | | 9/16n=3/3/4 | | p/16=-7 | | 85=-7x-5(x-5) | | 8(5)x=172 |

Equations solver categories